Transformation of Public Service: Rise of Technology, AI and Automation - Neupane, Aarati (Prashasan: The Nepalese Journal of Public Administration, 2023)
The rapid advancement of technology has proven beneficial for enhancing efficiency, transparency, responsiveness, and effectiveness in the administration of public services. The internalization of technological innovations, including AI and automation, has become imperative to address the increasing needs and expectations of citizens in modern governance. Various developed and developing countries have revolutionized public services through the adoption of AI and automation. Nepal has made strides in digital governance, advancing from a paper-based form of governance to digital governance. Moreover, the Digital Nepal Framework aspires to restructure the economy through increased service delivery, production, and productivity by harnessing digital technology. The issues of the digital divide, ethical and responsible adoption of AI, citizen engagement and participation, and inclusiveness have been challenging. The government should prioritize investments in digital infrastructure, encourage tech innovations, and promote capacity development in the field of technology.